Effect of freezing on the rheological, chemical and colour properties of Serpa cheese - Alvarenga, Nuno Bartolomeu (2013)
The effect of freezing on the properties of a raw ewes’-milk semi-soft cheese (Serpa cheese) was studied using small amplitude oscillatory (SAOS) and texture measurements, colour and chemical parameters. The freezing was introduced at three different stages of the ripening process (28, 35 and 42 days), and the cheeses were maintained frozen for 12 months. Cheeses were submitted to a slow or fast freezing method, and to different storage temperatures: −10 and −20°C (three replicates for each set conditions). Chemical data showed that only the proteolysis indicators exhibited differences between frozen and non-frozen samples; frozen samples showed higher values of NPN than the non-frozen samples, indicating that the freezing process did not prevent the secondary proteolysis of cheese. Frozen samples showed a significantly (P<0·05) stronger structure than the non-frozen, as indicated by hardness. However, the differences between the frozen and non-frozen samples were not significantly for storage modulus (G′1Hz) and loss tangent (tan δ1Hz) (P>0·05). Freezing affected mainly colour parameters: frozen samples were more luminous, and more yellow-green. The results allowed us to conclude that the damages caused by freezing to cheese properties could be minimized if this type of storage is introduced at the end of ripening (42 d) using a freezing temperature of −20°C.